2021
DOI: 10.1128/mbio.03481-20
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Emergence of Azithromycin Resistance in Multiple Genotypes of Typhoidal Salmonella

Abstract: The rising prevalence of antimicrobial resistance in Salmonella enterica serovars Typhi and Paratyphi A, causative agents of typhoid and paratyphoid, have led to fears of untreatable infections. Of specific concern is the emerging resistance against azithromycin, the only remaining oral drug to treat extensively drug resistant (XDR) typhoid. Since the first report of azithromycin resistance from Bangladesh in 2019, cases have been reported from Nepal, India, and Pakistan. The genetic basis of this resistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 41 publications
4
61
1
Order By: Relevance
“…Isolates from Dhaka 10 have also been reported to be multi-drug resistant carrying genes conferring additional resistance to chloramphenicol, ampicillin and co-trimoxazole. Recent studies 15 has revealed that these mutations now appear to be emerging in more non-H58 genotypes in Dhaka from 2016 onwards including genotypes 2.3.3, 3.2.2, and 3.3.2.…”
Section: Resultsmentioning
confidence: 99%
“…Isolates from Dhaka 10 have also been reported to be multi-drug resistant carrying genes conferring additional resistance to chloramphenicol, ampicillin and co-trimoxazole. Recent studies 15 has revealed that these mutations now appear to be emerging in more non-H58 genotypes in Dhaka from 2016 onwards including genotypes 2.3.3, 3.2.2, and 3.3.2.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, other AcrB-Sa mutants have been observed, causing untreatable infections in Nepal, Bangladesh, India and Pakistan, in both Salmonella Typhi [85][86][87][88] and Salmonella Paratyphi A [85,88], summarized in Table 9. These clinical isolates are resistant to azithromycin (macrolide) by the mutations R717Q and R717L in AcrB-Sa.…”
Section: Acrb-sa Mutants Cause Fluoroquinolone (G288) and Macrolide (R717) Resistancementioning
confidence: 99%
“…Of these, 32 Salmonella Typhi and 6 Salmonella Paratyphi A isolates had a significantly high azithromycin MIC (>32 mg ml −1 ). All of these 32 highly resistant Typhi isolates had the R717 mutation (29 R717Q and 3 R717L), and five Paratyphi A isolates had the R717Q mutation [88]. It is clear that the spontaneous and divergent emergence of the "R717 mutations" in AcrB-Sa should raise great concern for the treatment of typhoid fever by macrolides.…”
Section: Acrb-sa Mutants Cause Fluoroquinolone (G288) and Macrolide (R717) Resistancementioning
confidence: 99%
“…The recent worrisome trend among some XDR S. Typhi includes a correlation between efflux pump mutations and azithromycin resistance. For instance, a point mutation(s) on the antibiotic-binding subunit AcrB of the tripartite AcrAB-TolC efflux pumps (e.g., R717Q or R717L) has recently been correlated to azithromycin-resistance among some S. Typhi and S. Paratyphi A clinical isolates (19,25,26).…”
Section: Molecular Basis Of Third-generation Cephalosporin-resistance Among Xdr S Typhi Isolatesmentioning
confidence: 99%
“…They usually function as independent units in the IM to translocate antibiotics across the membrane bilayer, followed by their cooperation with RND-type efflux pumps to pump out antibiotics across the entire cell envelope (24). In typhoidal Salmonella, point mutations at amino acid position 717 (R717Q or R717L) on AcrB, the antibiotic-binding subunit of the RND-type AcrAB-TolC efflux pump, have been correlated with resistance to azithromycin in S. Typhi and S. Paratyphi A, respectively (19,25,26).…”
Section: Introductionmentioning
confidence: 99%